Digital Land Certification in Indonesia: A Trilemma of Law, Tech, and Society - Mohammad Roesli; Yeni Ika Pratiwi (International Journal of Law and Society, 2026)
This study examines the prospects and challenges of digitizing land certificates in Indonesia, with a focus on legal certainty within the Fourth Industrial Revolution (4IR) framework. Through a socio-legal comparative case study of three distinct regions: Jakarta (high-capacity urban), Yogyakarta (hybrid socio-cultural), and East Nusa Tenggara (low-resource rural), data were collected via semi-structured interviews (n=45). Focus Group Discussions (FGDs) (n=12 sessions), field observations, and normative legal analysis. The findings reveal a clear cross-regional pattern: Jakarta demonstrates strong gains in transparency and efficiency through blockchain pilots; Yogyakarta shows mixed outcomes shaped by digital literacy and gender dynamics; while East Nusa Tenggara experiences net exclusion due to infrastructure deficits. Digitization potential is critically hampered by three interlocking barriers: (1) legal inconsistencies (vertical conflicts within agrarian law hierarchies and horizontal misalignment between UUPA and digital transaction laws); (2) technological disparities (stark digital divide excluding rural communities); and (3) socio-economic exclusion (low digital literacy and gender-based barriers). The study reconceptualizes legal certainty as a multiplex construct, simultaneously technical, legal, and social, and offers an integrated governance-centric framework comprising legal harmonization, tiered technological rollout, and participatory design. It contributes to SDG 16 (peace, justice, and strong institutions) and SDG 9 (innovation and infrastructure).